Multiple-high-order pole solutions for the NLS equation with quartic terms. (August 2022) - Wen, Li-Li; Fan, En-Gui; Chen, Yong
Abstract: The aim of this article is to investigate the multiple-high-order pole solutions to the focusing NLS equation with quartic terms (QNLS) under the non-vanishing boundary conditions (NVBC) via the Riemann–Hilbert(RH) method. The determinant formula of multiple-high-order pole soliton solutions for NVBC is given. Further the double 1 n d -order, mixed 2 n d - and 1 n d -order pole solutions are obtained.